Experiment on wax precipitation property of waxy crude oil based on DSC - GUO Liping; YI Bo; CHEN Rui; FENG Yaoguo (You-qi chuyun, 2023)
Wax precipitation property of waxy crude oil is a basic parameter for the economic & safe operation and flow security assurance technology of waxy crude oil pipeline transportation. The conventional Differential Scanning Calorimetry (DSC) experimental method has its accuracy greatly dependent on the experimental process, with poor repeatability of measurement results. Given this reason, experiment was conducted with two methods: DSC and the Modulated Differential Scanning Calorimetry (MDSC). Meanwhile, the wax precipitation property of waxy crude oil was analyzed. The results show that the cooling rate is more influential on the wax precipitation property of the waxy crude oil that is measured by the conventional DSC method. Under the same conditions, both of the wax precipitation temperature and the cumulative amount of precipitated wax measured by MDSC are obviously higher than those measured by DSC. The final temperature of wax crystal precipitation in MDSC experiment is obviously higher than that in the conventional DSC experiment, whereas there is no significant difference in the two cumulative amounts of precipitated wax at the final temperatures in the two experiments, and the MDSC experiment appears to be less affected by the cooling rate. Judging from the effect of obtaining the wax precipitation property of waxy crude oil, MDSC experimental results are superior to the conventional DSC experiment. The research results could provide a basis for the selection of experimental methods and conditions for the wax precipitation property of waxy crude oil.